1990
DOI: 10.1002/mpo.2950180417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of naevocytic naevi after chemotherapy for childhood cancer

Abstract: The frequency of naevocytic naevi (moles) in patients with childhood haematologic malignancies was studied. All patients had received multiple chemotherapy. The majority had also received cranial irradiation as part of their central nervous system leukaemia/lymphoma prophylaxis. Total body mole counts of the patients were compared with those of their healthy brothers and sisters. The median number of moles in the patient group was 20.0 (n = 79), in the healthy sibs 11.0 (n = 88). In two subgroups mole counts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Internal malignancy with or without the administration of chemotherapy, is another setting in which eruptive nevi have been reported. [19][20][21][22][23] Arguably, immunosuppression may be the common denominator in these patient populations. Other case reports of eruptive nevi include associations with Addison's disease 24 and psoralen-UVA, 25 and in isolation without any apparent disease association.…”
Section: Discussionmentioning
confidence: 99%
“…Internal malignancy with or without the administration of chemotherapy, is another setting in which eruptive nevi have been reported. [19][20][21][22][23] Arguably, immunosuppression may be the common denominator in these patient populations. Other case reports of eruptive nevi include associations with Addison's disease 24 and psoralen-UVA, 25 and in isolation without any apparent disease association.…”
Section: Discussionmentioning
confidence: 99%
“…Acral naevi (occurring on palms and soles), which are generally uncommon, were increased in both groups of oncology patients. In another study in The Netherlands (de Wit et al, 1990), the median number of naevi in subjects who had received chemotherapy for childhood cancer was found to be increased (P < 0.05), this time in comparison with siblings. A recent study in Glasgow showed that total body naevus counts were significantly increased in 22 children who were followed-up 3 years after starting maintenance chemotherapy for leukaemia (Baird et al, 1992), though comparison median naevus counts were only available according to decade of age for children assessed in a separate crosssectional study (MacKie et al, 1985).…”
mentioning
confidence: 88%
“…We examined approximately 90% of patients who had ever received treatment for childhood cancer in Queensland over the last two decades and compared the occurrence of melanocytic naevi to that in controls of the While previous findings have been suggestive of a general association between chemotherapy and naevi, there is no firm evidence. Two case-control studies which found a positive association were based on relatively small numbers de Wit et al, 1990), while in a follow-up study which reported increased numbers of naevi in children 3 years after commencement of maintenance chemotherapy, there were potential problems with the comparison subjects who were ascertained some years earlier and whose naevi were counted using different criteria, in a cross-sectional study (Baird et al, 1992). Furthermore, all these studies de Wit et al, 1990;Baird et al, 1992) differed from the present study in that they were conducted in populations with low background levels of sun exposure.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that cytostatic treatment is associated with an increase in melanocytic nevi (moles), a strong risk factor for melanoma, in long term cancer survivors (32). However, thus far no increase in the incidence of melanoma in long term cancer survivors has been reported (33).…”
Section: Van Der Does-van Den Berg Et a Lmentioning
confidence: 99%